2022
DOI: 10.3889/oamjms.2022.8753
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Purple Sweet Potato Extract on Antituberculosis-Induced Liver Toxicity

Abstract: BACKGROUND: The proportion of antituberculosis-induced liver injury on tuberculosis patients showed a relatively high incidence in many countries. Hepatic damage induced by antituberculosis drugs might potentially fatal. Isoniazid (INH) and rifampicin (RIF) are two main components of antituberculosis with crucial role for the incidence of liver injury. One of the herbal remedies that pose hepatoprotective action is purple sweet potato. Hepatoprotective action of purple sweet potato extract has been proved to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to a previous study reported by Soedarsono et al [35], rifampicin activates isoniazid hydrolase when used together, which increases the production of hydrazine and may account for their greater toxicity. Moreover, Artini et al [36] demonstrated that INH-induced oxidative stress can promote apoptotic conditions in cells, as indicated by the overexpression of the hepatic caspase-3 levels.…”
Section: Well-dispersible Nanoparticles (Sps-senps) [6 and 22]mentioning
confidence: 99%
“…According to a previous study reported by Soedarsono et al [35], rifampicin activates isoniazid hydrolase when used together, which increases the production of hydrazine and may account for their greater toxicity. Moreover, Artini et al [36] demonstrated that INH-induced oxidative stress can promote apoptotic conditions in cells, as indicated by the overexpression of the hepatic caspase-3 levels.…”
Section: Well-dispersible Nanoparticles (Sps-senps) [6 and 22]mentioning
confidence: 99%
“…The two pathways -intrinsic and extrinsic-are involve in RGC apoptosis. These routes connect to Caspase-3, a cysteine protease, and Bax, a Bcl-2 family [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%